An Ambulatory Polysomnography Study of the Post-traumatic Nightmares of Post-traumatic Stress Disorder. Issue 1 (22nd November 2017) - Phelps, Andrea J; Kanaan, Richard A A; Worsnop, Christopher; Redston, Suzy; Ralph, Naomi; Forbes, David
Abstract: Study Objectives: This study used ambulatory polysomnography (PSG) to investigate post-traumatic nightmares of post-traumatic stress disorder (PTSD). The key research question was whether post-traumatic nightmares occur in both rapid eye movement (REM) and non-REM sleep, and if so, whether nightmares in each sleep stage differed in content, phenomenology, and heart rate response. Underlying sleep disorders were investigated in an exploratory way. Methods: Thirty-five treatment-seeking veterans, current serving military members, and emergency service personnel undertook full PSG using the Compumedics (Melbourne, Australia) SomtePSG V1 system, during an inpatient psychiatric admission. The PSG recording included an event button to be pressed when a nightmare occurred, allowing us to determine the stage of sleep, changes in heart rate, and associated sleep events. The content and phenomenological features of participants' nightmares were recorded. Results: Of the 35 participants, 29 reported a nightmare during their sleep study, but only 21 pressed the event button and could recall the content of one or more nightmare. This yielded sleep and nightmare data for 24 nightmares. Of the 24, 10 nightmares arose from REM sleep and 14 from non-REM (stages N1 and N2). Seven were accurate trauma replays and 17 were non-replay or a mixture of replay and non-replay. Most nightmares were associated with respiratory or leg movement events and increase in heart rate on awakening. Conclusions: Post-traumatic nightmares of PTSD occur in both REM and non-REM sleep and are commonly associated with other sleep disturbances. These findings have important treatment implications.